Existence results for chemotaxis-shallow water system with degenerate viscosity coefficients and initial vacuum. (November 2019) - Wang, Zhigang
Abstract: This paper is concerned with the Cauchy problem of the chemotaxis-shallow water system with degenerate viscosity coefficients. A local existence of the unique regular solution is established when the initial data are arbitrarily large and include vacuum. Moreover, a Beal–Kate–Majda type blow-up criterion is provided.